Cross-cultural adaptation and validation of Bahasa Malaysia version of the Eating Disorder Examination Questionnaire (EDE-Q) - Musa, Ramli; Haniff, Jamaiyah; Muhammad, Noor Azimah; Omar, Khairani (2010)
Introduction: As eating disorders such as anorexia nervosa and others are generally becoming more prevalent, it is essential to have a culturally accepted and locally validated questionnaire that is able to detect abnormal eating habits. Objective: To translate the Eating Disorders Examination Questionnaire (EDE-Q) into Bahasa Malaysia (BM) and to determine the construct validity, reliability and other psychometric properties of the BM version. Method: Two parallel forward and backward translations were done in BM in accordance to guideline. Its validation was determined by using confirmatory factor analysis among 298 secondary school children. Results: The BM EDE-Q had very good internal consistency with global Cronbach’s alpha value of 0.879. For construct validity, majority of the items managed to produce values of more than 0.4 for confirmatory factor analysis with four unforced distinct factors detected. Conclusions: Analyses of reliability and validity of this BM version of EDE-Q yielded satisfactory results. The BM version produced in this study had good psychometric properties and it is applicable to the Malaysian population. Findings indicated that cultural factors in eating habits certainly influences the effort to adapt the questionnaire within a Malaysian setting.